Teaching Academic Integrity in Quebec Universities: Roles Professors Adopt - Peters, Martine; Boies, Tessa; Morin, Sonia (Frontiers in Education, 2019)
The habits of university students today have changed drastically thanks to the technological tools at their disposal and the access to an enormous amount of information on the web, which they can copy, use and reference in their assignments. Unfortunately, the line has become blurred about what is and what isn’t permitted by their professors and their universities, sometimes resulting in students committing plagiarism. Research has shown that many students arrive at university unprepared. They lack the informational skills needed to research and choose the information relevant for their assignments, the writing skills necessary to properly integrate the found information with paraphrases or quotations, or the referencing skills to provide their sources in order to write their assignments with integrity. In this research, we aimed to examine how professors in six different universities viewed their role in the teaching of academic integrity by means of educating students on informational, writing, and referencing skills as well as teaching their students about plagiarism prevention. Forty-nine professors and lecturers were interviewed about their role in the teaching of various skills. Results show that there were four types of information searching assignments required by the professors: searches for published information, searches for authentic contextual information, searches limited to the handouts given to the students and no information research required. Seven roles emerged from the data, from the Ambassador professor who takes full responsibility for the teaching of skills to prevent plagiarism to the Detached professor, who completely dissociates from this responsibility for different reasons. Recommendations are presented on how to encourage professors to adopt the four roles of the “Integrity Ambassador”: the intermediary who promotes the discovery of all services available to students; the awakener, who encourage students’ appreciation of learning for the sake of learning; the accompanist, who guides and supports students with direct interventions in class so that they develop the skills and knowledge necessary to write their assignments with integrity; and finally, by being a model, the Integrity Ambassador cultivates a climate of integrity in class and in the university, showing how one can lead an academic life with integrity.